2021
DOI: 10.1002/anie.202105883
|View full text |Cite
|
Sign up to set email alerts
|

Introducing Intermolecular Cation‐π Interactions for Water‐Stable Low Dimensional Hybrid Lead Halide Perovskites

Abstract: Optoelectronically active hybrid lead halide perovskites dissociate in water.T oprevent this dissociation, here,we introduce long-range intermolecular cation-p interactions between A-site cations of hybrid perovskites.A na romatic diamine like 4,4'-trimethylenedipyridine,i fp rotonated, can show al ong-range cation-p stacking, and therefore,s erves as our A-site cation. Consequently,4,4'-trimethylenedipyridinium lead bromide [(4,4'-TMDP)Pb 2 Br 6 ], ao ne-dimensional hybrid perovskite,r emains completely stabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
78
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 58 publications
3
78
0
Order By: Relevance
“…A1 Dn etwork of the Pb-Br octahedral dimers can be observed along the "bc"c rystal plane (right panel in Figure 2). Interestingly,t he 4,4'-TMDP cations are arranged in such aw ay that the ammonium ions on one 4,4'-TMDP [17] Angewandte Chemie Forschungsartikel 18414 www.angewandte.de cation are exactly on top of the p-electron rings of the adjacent 4,4'-TMDP cation. This arrangement gives rise to along-range cation-p stacking along the "b"crystallographic direction.…”
Section: Synthesis and Structure Showing Cation-p Stackingmentioning
confidence: 99%
See 1 more Smart Citation
“…A1 Dn etwork of the Pb-Br octahedral dimers can be observed along the "bc"c rystal plane (right panel in Figure 2). Interestingly,t he 4,4'-TMDP cations are arranged in such aw ay that the ammonium ions on one 4,4'-TMDP [17] Angewandte Chemie Forschungsartikel 18414 www.angewandte.de cation are exactly on top of the p-electron rings of the adjacent 4,4'-TMDP cation. This arrangement gives rise to along-range cation-p stacking along the "b"crystallographic direction.…”
Section: Synthesis and Structure Showing Cation-p Stackingmentioning
confidence: 99%
“…Crystal structure of (4,4'-TMDP)Pb 2 Br 6 showing cation-p stacking:T he left panel depicts the crystal structure viewed along the "ac" crystallographic plane, showing edge shared Pb-Br octahedrald imers separated by 4,4'-TMDP cations. The right panel depicts the cation-p stacking (shown by dashed black lines) between the 4,4'-TMDP cations along the "b"crystallographic direction and the 1D network of Pb-Br octahedrald imers [17].…”
mentioning
confidence: 99%
“…[ 31 ] For example, Sn 2+ ‐based (C 8 H 14 N 2 ) 2 SnBr 6 reported by our group and Pb 2+ ‐based ( 4,4′‐TMDP )Pb 2 Br 6 by Nag's group show the good environmental stability due to the existence of intermolecular π–π interaction. [ 32,33 ] However, the large optical band gap values ( E g > 3 eV) mean that they can only be excited by ultraviolet light. It is found that a large number of Cu(I)‐based metal halide cluster compounds show the relatively small optical bandgap values (2 eV < E g < 3 eV) compared with ns 2 ‐based 0D metal halide hybrids.…”
Section: Introductionmentioning
confidence: 99%
“…[31] For example, Sn 2+ -based (C 8 H 14 N 2 ) 2 SnBr 6 reported by our group and Pb 2+ -based (4,4′-TMDP)Pb 2 Br 6 by Nag's group show the good environmental stability due to the existence of intermolecular π-π interaction. [32,33] However, the large optical band The discovery of rare-earth free luminescent materials with blue-light-excitable characteristic is of great importance for solid-sate lighting applications. Herein, a Cu(I)-based 0D luminescent hybrid (1,3-dppH 2 ) 2 Cu 4 I 8 •H 2 O is synthesized by a facile solution method, and it shows the orange-red emission peaking at 625 nm upon 460 nm excitation.…”
mentioning
confidence: 99%
“…However, to the best of our knowledge, there was no report of THG in 1D lead halides until a very recent report by us. 32 Furthermore, LD perovskitoids show strong photoluminescence (PL) from excitonic recombination. 33,34 In addition, a broad thermally activated emission far from the band edge, known as self-trapped excitonic emission, is also observed.…”
Section: ■ Introductionmentioning
confidence: 99%